Synthetic bone as a solution for halal bone grafts implantation: demand for bone graft has been increasing steadily - Sopyan, Iis; Alqap, Asep Sofwan Faturrahman (TM-Info-Media Sdn. Bhd., 2009)
The use of allografted bone substance requires several considerations: pathological clearance to ensure that the bone is free from any disease or harmful bacteria or viruses, the method is legal, allografting is an acceptable culture in the society, etc. Regarding the use of xenografts, pig bones are the most similar to human bones among pigs, mice and rats. Therefore, pig bone is usually used as a model for studyng the molecular genetics of bone-related disorder or even for xenografting. Moreover, with regard to macro- and microstructure, composition and suitability for remodeling, again pig bone is the most similar to human bone among porcine, canine, sheep, goat and rabbit.